Innovative mechanisms for modernizing the education and science system of Ukraine - Zhelezniakova, Natalia; Prosolenko, Kostyantyn; Molodan, Volodymyr; Aleksandrova, Tetiana (ВСП «Харківський торговельно-економічний фаховий коледж ДТЕУ», 2026)
Currently, the development of Ukrainian society is characterized by profound transformational processes driven by globalization, digitalization, and integration into the European educational and scientific space. Under conditions of full-scale war, economic instability, and the need for post-war reconstruction, Ukraine's education and science system constitutes a strategic resource for the country’s sustainable socio-economic development. Innovative mechanisms for modernizing the education and science system involve not only updating educational content to align with contemporary labor market requirements and technological advancements, but also transforming governance models, financial instruments, and quality assurance systems, strengthening academic integrity, and fostering the integration of science with business. An important role is played by the digital transformation of the educational environment, the development of distance and blended learning, support for interdisciplinary research, and the commercialization of scientific outputs. Therefore, the modernization of the educational and scientific spheres requires the implementation of innovative mechanisms capable of ensuring their flexibility, competitiveness, and compliance with international standards.
Keywords: science system; Ukraine's education; digitalization of the education; European higher education; 2026а